Cu-Al2O3/Water hybrid nanofluid through a permeable surface in the presence of nonlinear radiation and variable thermal conductivity via LSM. (November 2018) - Usman, M.; Hamid, M.; Zubair, T.; Ul Haq, Rizwan; Wang, W.
Highlights: Flow model is presented for Cu-Al2 O3 /Water hybrid nanofluid and ethylene–glycol based Cu -nanoparticles. Mathematical modeling is constructed for time-dependent thermal conductivity on rotating flow. Least square Galerkin method (LSGM) is adopted to determine the solution of complex nature model. Solutions are obtained for skin friction and Nusselt number for each kind of nanoparticles mixture. Abstract: This paper scrutinizes the significant effects of nonlinear thermal radiation and time-dependent thermal conductivity due to rotating flow of Cu-Al2 O3 -water hybrid nanofluid over a three-dimension stretching sheet. The influence of bouncy forces and magnetic field are also considered. The obtained set of partial differential equations (PDEs) converted to a simplified set of ordinary differential equations (ODEs) by introducing the feasible similarity transformation. Least square method (LSM) is adopted to examine the solution of developed model. The obtained solutions are compared with the well-known numerical technique: Runge-Kutta method of order fourth (RK-4). Significant influence of various physical parameters on the velocities and temperature are explained in detailed through graphical representations. Behavior of skin friction coefficient and local Nusselt number due the variation of numerous parameters also discussed in detail. The velocity profiles F ′ ( η ) and G ′ ( η ) for the case of Cu-Al2 O3 -water are dominant as compare to Cu -water and Al2 O3 -water while the fluid temperature is dropped for Cu-Al2 O3 -water case as compare to Cu -water and Al2 O3 -water. It is noticed that, variation in the Hartmann, porosity and suction/injection parameters cause to increase the friction at the surface. Opposite behavior of skin friction coefficient is observed by increasing the strength of rotational, Grashof number and slip parameter. Obtained results and comparative study witnesses that the least square technique is well-matched with existing results and it can be applied for complex nature models.